Evaluation of the Effect of Non-Surgical Periodontal Treatment on Oral Health-Related Quality of Life in Patients with Periodontitis at Different Stages - Mahmure Ayşe Tayman (Cumhuriyet University, 2022)
Aim: To determine the effect of non-surgical periodontal treatment (NSPT) on oral health-related-quality-of-life (OHRQoL) in individuals with periodontitis at different stages. Materials and Methods: Full-mouth clinical periodontal parameters [plaque-index (PI), gingival-index (GI), probing-pocket-depth (PD), bleeding-on-probing (BOP), clinical-attachment-loss (CAL)] of 119 healthy individuals aged 24 to 64 years just before and six-weeks after NSPT were obtained and the mean was calculated. Oral hygiene instructions were given. The Oral-Health-Related-Quality-of-Life-United-Kingdom (OHRQoL-UK) scale was used to measure the positive and negative effects of NSPT on OHRQoL. Sociodemographic data (age, gender, education and income status, reason for admission to the hospital, use of toothbrush, other cleaning tools, removable prosthesis and smoking) of the participants were recorded using a multiple choice questionnaire. Results: The use of toothbrushes and cleaning device increased in all phases after the treatment (p<0.01). Ages of individuals in stage-IV were higher than other stages (p>0.05). Individuals in stage-III (p=0.01) and IV had fewer teeth than other stages (p=0.01), while the use of removable prosthesis was higher (p<0.05). Clinical periodontal parameters decreased significantly in all stages after treatment and showed improvement (p<0.01). When all stages before and after treatment were compared within themselves, there were significant differences in the total score of OHRQoL between stages I-III, I-IV, II-III and II-IV (p<0.05). It was observed that all OHRQoL scores increased when compared before and after treatment in terms of symptoms, physical, psychological and social status (p<0.01). Conclusion: NSPT provides a significant improvement in the OHRQoL of individuals in all stages of periodontitis.